Long non-coding RNAs: Mechanism of action and functional utility - Shakil Ahmad Bhat; Syed Mudasir Ahmad; Peerzada Tajamul Mumtaz; Abrar Ahad Malik; Mashooq Ahmad Dar; Uneeb Urwat; Riaz Ahmad Shah; Nazir Ahmad Ganai (Non-coding RNA Research, 2016)
Recent RNA sequencing studies have revealed that most of the human genome is transcribed, but very little of the total transcriptomes has the ability to encode proteins. Long non-coding RNAs (lncRNAs) are non-coding transcripts longer than 200 nucleotides. Members of the non-coding genome include microRNA (miRNA), small regulatory RNAs and other short RNAs. Most of long non-coding RNA (lncRNAs) are poorly annotated. Recent recognition about lncRNAs highlights their effects in many biological and pathological processes. LncRNAs are dysfunctional in a variety of human diseases varying from cancerous to non-cancerous diseases. Characterization of these lncRNA genes and their modes of action may allow their use for diagnosis, monitoring of progression and targeted therapies in various diseases. In this review, we summarize the functional perspectives as well as the mechanism of action of lncRNAs. Keywords: LncRNA, X-chromosome inactivation, Genome imprinting, Transcription regulation, Cancer, Immunity